2018
DOI: 10.4314/ijbcs.v12i1.27
|View full text |Cite
|
Sign up to set email alerts
|

Dynamique de la régénération naturelle des essences commerciales sur les routes secondaires de différents âges de l’UFA 09-003 (Djoum, Cameroun)

Abstract: RESUMELe Cameroun dispose d'une superficie de forêt estimée à 22 millions d'hectares qui assure des fonctions économiques, sociales et culturelles. Compte tenu de l'importance des services rendus, la forêt camerounaise devrait être gérée de manière durable, ce qui n'est pas encore le cas. L'étude menée dans l'Unité Forestière d'Aménagement (UFA) 09-003 à Djoum avait pour objectif d'évaluer la régénération naturelle des essences commerciales sur les routes secondaires de différents âges. L'échantillonnage d'une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…These results also show a very high diversity of woody species in secondary or heavily disturbed areas. Our results confirm the assumptions of [62], who confirmed that recently disturbed areas harbor a high diversity of regenerating woody species. On the other side, our results tend to confirm the works of [16] who demonstrated 321 ligneous species belonging to 26 species.…”
Section: The Specific Richness and The Intra And Inter Annual Allowab...supporting
confidence: 91%
See 1 more Smart Citation
“…These results also show a very high diversity of woody species in secondary or heavily disturbed areas. Our results confirm the assumptions of [62], who confirmed that recently disturbed areas harbor a high diversity of regenerating woody species. On the other side, our results tend to confirm the works of [16] who demonstrated 321 ligneous species belonging to 26 species.…”
Section: The Specific Richness and The Intra And Inter Annual Allowab...supporting
confidence: 91%
“…Also, [58] tend to confirm that in the tropical forest of Africa, zoochory is the most widespread mode of dissemination with approximately 80% to 90%. In the case of the present study, this could be justified by the fact that abandoned secondary roads would be much more attractive to the animals due to abundance of herbs as food sources, as has been demonstrated for gorillas [59] [60] [61] [62]. Recently, in central Africa, the creation of roads and skid trails by logging operations leads to changes in the structure of forest landscapes that could influence wildlife movements.…”
Section: Stationsmentioning
confidence: 73%